2022
DOI: 10.3389/fncel.2022.1022431
|View full text |Cite
|
Sign up to set email alerts
|

What microglia depletion approaches tell us about the role of microglia on synaptic function and behavior

Abstract: Microglia are dynamic cells, constantly surveying their surroundings and interacting with neurons and synapses. Indeed, a wealth of knowledge has revealed a critical role of microglia in modulating synaptic transmission and plasticity in the developing brain. In the past decade, novel pharmacological and genetic strategies have allowed the acute removal of microglia, opening the possibility to explore and understand the role of microglia also in the adult brain. In this review, we summarized and discussed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 265 publications
(435 reference statements)
0
11
0
Order By: Relevance
“…In contrast, other studies reported an increase in hippocampal LTP in full knockouts (Maggi et al, 2011; Milior et al, 2016). Importantly, in addition to methodological differences, the region‐specific role of microglial phenotypes and properties, including CX3CR1‐signalling, has previously been discussed as a reason for these discrepancies, which have also to be considered in comparison with our motor cortical data (Basilico et al, 2022). Another molecular mechanisms underlying our results could be inferred from our previous finding that brain‐derived neurotrophic factor (BDNF) release plays a key role in the neuroplastic effects of DCS (Fritsch et al, 2010; A. K. Gellner et al, 2019) and from others showing that microglia‐derived BDNF is essential for motor cortical plasticity (Parkhurst et al, 2013).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast, other studies reported an increase in hippocampal LTP in full knockouts (Maggi et al, 2011; Milior et al, 2016). Importantly, in addition to methodological differences, the region‐specific role of microglial phenotypes and properties, including CX3CR1‐signalling, has previously been discussed as a reason for these discrepancies, which have also to be considered in comparison with our motor cortical data (Basilico et al, 2022). Another molecular mechanisms underlying our results could be inferred from our previous finding that brain‐derived neurotrophic factor (BDNF) release plays a key role in the neuroplastic effects of DCS (Fritsch et al, 2010; A. K. Gellner et al, 2019) and from others showing that microglia‐derived BDNF is essential for motor cortical plasticity (Parkhurst et al, 2013).…”
Section: Discussionmentioning
confidence: 91%
“…These regions might be additionally relevant for the phenotypes we and others observed. Moreover, regional differences regarding microglia properties and their impact on neuroplasticity, even between different cortical areas, have been reported (Basilico et al, 2022; Tan et al, 2020). Consequently, our data exclusively from the motor cortex have to be carefully interpreted in comparison to studies from other brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…How then does microglial activation mediate the rapid antidepressant effect of zymosan A? In the resting state, microglia are mainly responsible for maintaining brain homeostasis by clearing neuronal debris (Cowan and Petri, 2018) and altering synaptic plasticity (Basilico et al ., 2022). We hypothesize that zymosan A first activates microglia in the hippocampus, thereby promoting excitatory neurotransmission and producing antidepressant effects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, various BAFF B cell survival signal inhibitors (e.g., Belimumab) are being developed or are currently deployed in clinical populations. Treatments developed for other therapeutic applications that are directed against other central [e.g., microglial depletion with colony stimulating factor 1 receptor inhibitors (PLX3397) ( Basilico et al, 2022 )] or systemic [e.g., anti-CD3 muromonab ( Kuhn and Weiner, 2016 )] immune cell populations can be used for discerning the extent to which interactions with other cells types is an important mechanism by which B cells influence the response to stress. MAbs directed against distinct cytokines are also available.…”
Section: Research Toolsmentioning
confidence: 99%